Stratospheric intrusions, the Santa Ana winds, and wildland fires in Southern California. Issue 14 (23rd July 2015) - Langford, A. O.; Pierce, R. B.; Schultz, P. J.
Abstract: The Santa Ana winds of Southern California have long been associated with wildland fires that can adversely affect air quality and lead to loss of life and property. These katabatic winds are driven primarily by thermal gradients but can be exacerbated by northerly flow associated with upper level troughs passing through the western U.S. In this paper, we show that the fire danger associated with the passage of upper level troughs can be further increased by the formation of deep tropopause folds that transport extremely dry ozone‐rich air from the upper troposphere and lower stratosphere to the surface. Stratospheric intrusions can thus increase surface ozone both directly through transport and indirectly through their influence on wildland fires. We illustrate this situation with the example of the Springs Fire, which burned nearly 25, 000 acres in Ventura County during May 2013. Key Points: Synoptic flow associated with stratospheric intrusions can force Santa Ana winds Descent of dry lower stratospheric air to the surface can foment wildfires Stratospheric intrusions can indirectly increase ozone by exacerbating wildfires